Second malignancies in multiple myeloma; emerging patterns and future directions. Issue 1 (March 2020) - Maclachlan, Kylee; Diamond, Benjamin; Maura, Francesco; Hillengass, Jens; Turesson, Ingemar; Landgren, C. Ola; Kazandjian, Dickran
Abstract: The changing landscape of treatment options for multiple myeloma has led to a higher proportion of patients achieving deep, long-lasting responses to therapy. With the associated improvement in overall survival, the development of subsequent second malignancies has become of increased significance. The risk of second malignancy after multiple myeloma is affected by a combination of patient-, disease- and therapy-related risk factors. This review discusses recent data refining our knowledge of these contributing factors, including current treatment modalities which increase risk (i.e. high-dose melphalan with autologous stem cell transplant and lenalidomide maintenance therapy). We highlight emerging data towards individualized risk- and response-adapted treatment strategies and discuss key areas requiring future research.